The Effect of Liability and ROE on Audit Delay in Listed Energy Sector Companies on the Indonesia Stock Exchange 2021-2023 - Fista Lindu Aprilia; Sherly Indah Kania; Echa Salsabilla; Marshanda Marshanda; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This study examines the impact of capital structure components, namely liabilities and equity, on the duration of audit delay in energy sector entities listed on the IDX during 2021-2023. Using quantitative methodology with multiple linear regression techniques, this study sets DER as a proxy for liabilities and ROE as a proxy for equity, while audit delay is measured nominally as the dependent variable. The research findings revealed a positive and significant effect of equity on audit delay with a coefficient value of 0.127 (sig. 0.025), while liabilities showed a significant negative effect with a coefficient of -0.050 (sig. 0.004). Simultaneous testing resulted in an F count of 13,386 with a significance of 0.000, proving that the two independent variables jointly affect audit delay. The research model is able to explain 55.3% of the variation in audit delay, as indicated by the Adjusted R Square value, with the remaining 44.7% explained by variables outside the model. Based on these results, this study recommends the importance of optimizing the capital structure of energy companies through efficient equity management and appropriate liability control to optimize audit completion time in the context of dynamic economic development.